Donor‐derived acute myeloid leukemia in solid organ transplantation. Issue 12 (8th September 2022) - Marchionni, Luigi; Lobo, Francisco Pereira; Kostadinov, Rumen; Serra, Anna; Besso, Federico Genzano; Deaglio, Silvia; Stratta, Piero; Berrino, Monica; Zanettini, Claudio; Imada, Eddie Luidy; Omar, Mohamed N.; Gaidano, Gianluca; et al.
Abstract: We report the transmission of acute myeloid leukemia (AML) undetected at donation from a deceased organ donor to two kidneys and one liver recipients. We reviewed the medical records, and performed molecular analyses and whole exome sequencing (WES) to ascertain AML donor origin and its molecular evolution. The liver recipient was diagnosed 11 months after transplantation and died from complications 2 months later. The two kidney recipients (R1 and R2) were diagnosed 19 and 20 months after transplantation and both received treatment for leukemia. R1 died of complications 11 months after diagnosis, while R2 went into complete remission for 44 months, before relapsing. R2 died 10 months later of complications from allogenic bone marrow transplantation. Microsatellite analysis demonstrated donor chimerism in circulating cells from both kidney recipients. Targeted molecular analyses and medical records revealed NPM1 mutation present in the donor and recipients, while FLT3 was mutated only in R1. These findings were confirmed by WES, which revealed additional founder and clonal mutations, and HLA genomic loss in R2. In conclusion, we report the first in‐depth genomic analysis of AML transmission following solid organ transplantation, revealing distinct clonal evolution, and providing a potential molecular explanation for tumor escape. Abstract : In‐depth genomic analysis of acute myeloid leukemia transmission following solid organ transplantation reveals distinct clonal evolution provides a molecular explanation for tumor escape.